The Interplay Between the Collaboration pattern (Individual-group) and the Cognitive Approach in the Flipped Classroom on the Promotion of the 9th Graders’ Academic Achievement in IT in the Sultanate of Oman - Almazroai, Sami khatar bin Makoum; Almosawi, Ali Sharaf; Khalifa, Zainab Mohammed (Journal of Educational and Psychological Sciences, 2020)
This study aims to find out the effect of the interaction between the collaboration pattern (individual- group) and the cognitive approach (independent/ dependent) on the cognitive field in the flipped classroom environment on improving grade 9 basic education students’ academic achievement in IT in the Sultanate of Oman. The researchers used the developmental approach (descriptive analytical and semi-experimental approach). The following two tools were used: The achievement test (pre/ post) to measure the achievement and the Embedded Figures Test to classify the (independent/ dependent) students on the cognitive field. The study consists of (119) female students of grade 9 basic education in the South Al Batinah Governorate in Sultanate of Oman, and they were divided into four experimental groups. The results of the research showed that the four groups in the post achievement test in IT subject were as follows: experimental (1) studied using the individual collaboration pattern (student/ teacher) and their cognitive style are independent of the cognitive field, they got an average (55.87). And experimental (2) studied using the individual collaboration pattern (student/ teacher) and their cognitive style is dependent on the cognitive field, they got an average (50.40). Whereas the experimental (3) that studied using the group collaboration pattern (students/ teacher) and their cognitive style are independent of the cognitive field an average (50.35). The experimental (4) students who studied using the group collaboration pattern (students/ teacher) and their cognitive style are dependent of the cognitive field an average of (59.14), although there are slight differences; however, it is not statistically significant at the level (α≤05,0) between the averages of the degrees of all four groups. Researchers believe that this is due to the primary effect of the difference in the cognitive style (independence versus dependence on the cognitive field) in the flipped class environment. And there is an effect of interaction between the collaboration pattern (individual- group) and the cognitive approach in the flipped classroom on the academic achievement. Based on the results, a set of recommendations and proposals were presented to activate the flipped classroom strategy and conduct subsequent research. In addition to a project plan to benefit from the research results.